SEROPREVALENCIA DE Toxoplasma gondii EN ALPACAS DE COMUNIDADES DE LA PROVINCIA DE CANCHIS, CUSCO - Ramírez R., Julia (2005)
The objective of the present study was to determine the seroprevalence ofToxoplasma gondii in alpacas of communities from the districts of Maranganí, Pitumarca,Checacupe and San Pablo, located in the province of Canchis, department of Cusco. Atotal of 272 blood samples were collected in March 2003, for the detection of antibodiesagainst T. gondii by the indirect immunofluorescence test (IFAT). The resultingseroprevalence was 35.7 ± 5.7%, without significant differences due to district, sex, andbreed; however, there was a significant association between age and IFAT value. Theresults of the present study agreed with other studies conducted in South Americancamelids in different localities in the south of Peru.